Electrocardiographic Follow‐Up of Biventricular Pacemakers - Barold, S. Serge (Ann Noninvasive Electrocardiol, 2005)
Multisite pacing for the treatment of heart failure has added a new dimension to the electrocardiographic evaluation of device function. During left ventricular (LV) pacing from the appropriate site in the coronary venous system, a correctly positioned lead V1 registers a right bundle branch block pattern with few exceptions. During biventricular stimulation associated with right ventricular (RV) apical pacing, the QRS is often positive in lead V1. The frontal plane QRS axis is usually in the right superior quadrant and occasionally in the left superior quadrant. Barring incorrect placement of lead V1 (too high on the chest), lack of LV capture, LV lead displacement or marked latency (exit block or delay from the stimulation site), ventricular fusion with the spontaneous QRS complex, a negative QRS complex in lead V1 during biventricular pacing involving the RV apex probably reflects different activation of an heterogeneous biventricular substrate (ischemia, scar, His‐Purkinje participation in view of the varying patterns of LV activation in spontaneous left bundle branch block) and does not necessarily indicate a poor (electrical or mechanical) contribution from LV stimulation. In this situation, it is imperative to rule out the presence of coronary venous pacing via the middle cardiac vein or even unintended placement of two leads in the RV. During biventricular pacing with the RV lead in the outflow tract, the paced QRS in lead V1 is often negative and the frontal plane paced QRS axis is often directed to the right inferior quadrant (right axis deviation). In patients with sinus rhythm and a relatively short PR interval, ventricular fusion with competing native conduction during biventricular pacing may cause misinterpretation of the ECG because narrowing of the paced QRS complex simulates appropriate biventricular capture. This represents a common pitfall in device follow‐up. Elimination of ventricular fusion by shortening the AV delay, is often associated with clinical improvement. Anodal stimulation may complicate threshold testing and should not be misinterpreted as pacemaker malfunction. One must be cognizant of the various disturbances that can disrupt 1:1 atrial tracking and cause loss of ventricular resynchronization. (1) Upper rate response. The upper rate response of biventricular pacemakers differs from the traditional Wenckebach upper rate response of conventional antibradycardia pacemakers because heart failure patients generally do not have sinus bradycardia or AV junctional conduction delay. The programmed upper rate should be sufficiently fast to avoid loss of resynchronization in situations associated with sinus tachycardia. (2) Below the programmed upper rate. This may be caused by a variety of events (especially ventricular premature complexes and favored by the presence of first‐degree AV block) that alter the timing of sensed and paced events. In such cases, atrial events become trapped into the postventricular atrial refractory period at atrial rates below the programmed upper rate in the presence of spontaneous AV conduction. Algorithms are available to restore resynchronization by automatic temporary abbreviation of the postventricular atrial refractory period.